Expansion of Multinational Corporations in de-facto States: The Case of Turkish Republic of Northern Cyprus - Demirel, Atay; Özdemir, Yonca (My University, 2021)
This article studies the dynamics of the existence and expansion of Multinational Corporations (MNCs) in the North Cyprus (Turkish Republic of Northern Cyprus, or the TRNC) within the context of embargoes and non-recognition in the international area. Therefore, we try to offer a better understanding on what mechanisms the MNCs use to expand their operations all over the world against extraordinary political situations. In this regard, the main research questions of this study are: ‘What are the dynamics of the existence and expansion of MNCs in the TRNC as an unrecognized state?’ and ‘How, and by using which tools and mechanisms do the MNCs exist, evolve, operate, and expand their capital in the TRNC market?’ Therefore, the mechanisms, tools, and processes used by the MNCs in their operating processes within the TRNC, and the dynamics and the forces behind investing in the TRNC despite the risks of illegality were investigated by conducting a field study. The field study was conducted through semi-structured in-depth interviews with nine participants who represented thirteen establishments of thirteen different MNCs operating in the TRNC. The findings of this research show that the MNCs use extraordinary tools and mechanisms in order to expand and legalize their investments in the TRN
Keywords: Tarih; Siyasi Bilimler; İşletme; Uluslararası İlişkiler